Management challenges for the fastest growing marine shipping sector in Arctic Canada: pleasure crafts. (29th September 2016) - Johnston, Margaret; Dawson, Jackie; De Souza, Elsa; Stewart, Emma J.
ABSTRACT: Changing environmental conditions in the Canadian Arctic are associated with an increase in marine tourism. A substantial decline in the extent of ice coverage in the summer season has resulted in greater accessibility for all categories of ships, and the tourism sector has been quick to respond to new opportunities. This increase in vessel traffic has raised significant issues for management, and particular concerns about the pleasure craft (non-commercial tourism) sector. This paper reports on research aimed at identifying change in the pleasure craft sector in Canadian Arctic waters since 1990; exploring management concerns held by stakeholders regarding changes in the sector; and, providing recommendations for government stakeholders. The paper is based on material gathered through an examination of existing data sources and stakeholder interviews ( n = 22). Analysis was aimed at understanding the rapid development of the sector and potential management strategies, including research needs. Analysis reveals a dramatic increase in annual vessel numbers, particularly from 2010 onwards. Management concerns of interviewees relate to implications of this growth in four areas: visitor behaviour; services, facilities and infrastructure; control; and, planning and development. The paper concludes by describing recommendations in the areas of research needs, regulation, and strategic development.